Respiratory Complications and Management in Duchenne Muscular Dystrophy and Amyotrophic Lateral Sclerosis - Huzarski, Filip; Marta, Patrycja Kinga; Ossolińska, Agata; Ferfecka, Gabriela Monika; Pawełek, Klaudia Anna; Stolarska, Lucyna; Rosa-Bończak, Magdalena; Morawiecka, Natalia; Kłosowicz, Weronika; Carlton, Olivier (Journal of Education, Health and Sport, 2025)
Introduction: Duchenne muscular dystrophy (DMD) and amyotrophic lateral sclerosis (ALS) are rare recessive genetic disorders. Both conditions lead to a range of systemic complications, including those affecting the respiratory system. Respiratory and cardiovascular complications are identified as the most common causes of mortality in individuals with DMD and ALS. Early diagnosis of reduced respiratory parameters can delay the progression of respiratory system involvement. Available therapies, including gene therapy, pharmacological approaches, and conservative methods, can slow disease progression and prevent respiratory complications. Aim of the study: The aim of this study was to analyze the available treatment methods for Duchenne muscular dystrophy (DMD) and amyotrophic lateral sclerosis (ALS), with a particular focus on respiratory complications. Materials and Methods: A non-systematic review of scientific articles was conducted using the keywords “spinal muscular atrophy,” “Duchenne muscular dystrophy,” and “respiratory.” The review was performed in the PubMed and Google Scholar databases, analyzing a total of 31 sources published between 2008 and 2024. Conclusions: Early diagnosis of DMD or ALS is crucial for extending life expectancy and delaying the onset of adverse complications, including those affecting the skeletal, cardiovascular, and respiratory systems. Currently, a broad range of therapeutic options is available to alleviate the daily challenges faced by patients and their families. Preventive measures and prompt responses to complications are essential to halt and delay further disease progression.